ANALYSIS OF REGIONAL INCOME DEVELOPMENT (Analisis Perkembangan Pendapatan Asli Daerah (PAD)) - Barmin Yusuf (Gorontalo Development Review, 2018)
Abstract The development budget needed every year is increasing. For this reason the regional government must improve regional economic development with a targeted level of GDP to be proportional to the amount of regional expenditure. The government also determines the sources of revenue from regions that can be extracted. One of the most important sources of income is original income (PAD). The original regional income consists of regional taxes and levies, profits of regionally owned companies, results of regional wealth management, and other local revenue. Regional tax is a source of local revenue which has a significant role in the formation of local revenue. The purpose of this study was to determine the development of Regional Original Revenue (PAD) in North Gorontalo District. The quantitative analysis model is used to analyze the development of North Gorontalo Regency's Local Revenue (PAD) using the Times Series or the time needed to look at revenue potential, namely the Linear Trend method. In the results of this study stated that the original revenue (PAD) of North Gorontalo Regency in the future will continue to increase. Where it can be seen that in 2015 the original regional income (PAD) of North Gorontalo District which was compared to 2014 would have decreased by 983,042,804 Rupiah and in 2016 increased by 1,733,651,583 Rupiah when compared to 2014, while in 2017 North Gorontalo regency's local revenue (PAD) when compared to 2014 increased by 4,450,345,972 Rupiah. Abstrak Anggaran pembangunan yang dibutuhkan tiap tahun semakin meningkat. Untuk itu pemerintah daerah harus meningkatkan perkembangan ekonomi daerah dengan tingkat PDB yang ditargetkan agar sebanding dengan jumlah pengeluaran daerah. Pemerintah pun menentukan sumber-sumber penerimaan daerah yang dapat digali. Salah satu sumber penerimaan paling penting adalah pendapatan asli daerh (PAD).Pendapatan asli daerah terdiri dari pajak dan retribusi daerah, keuntungan perusahaan milik daerah, hasil pengelolaan kekayaan daerah, dan lain-lain pendapatan asli daerah. Pajak daerah merupakan sumber pendapatan asli daerah yang cukup besar peranannya dalam terbentuknya pendapatan asli daerah.Tujuan dari penelitian ini adalah untuk mengetahui perkembangan Pendapatan Asli Daerah (PAD)  di Kabupaten Gorontalo Utara. Model analisis kuantitatif digunakan untuk menganalisa perkembangan Pendapatan Asli Daerah (PAD) Kabupaten Gorontalo Utara menggunakan Times Series atau runtut waktu untuk melihat potensi pendapatan yaitu metode Trend Linier.  Dalam hasil penelitian ini menyatakan pendapatan asli daerah (PAD) Kabupaten Gorontalo Utara dimasa yang akan datang akan terus mengalami peningkatan. Dimana dapat dilihat bahwa pada tahun 2015 pendapatan asli daerah (PAD) Kabupaten Gorontalo Utara yang ada apabila dibandingkan dengan tahun 2014 akan mengalami penurunan sebesar 983.042.804 Rupiah dan pada tahun 2016 meningkat sebesar 1.733.651.583 Rupiah apabila dibandingkan dengan tahun 2014, sedangkan tahun 2017 pendapatan asli daerah (PAD) Kabupaten Gorontalo Utara apabila dibandingkan dengan tahun 2014 meningkat sebesar 4.450.345.972 Rupiah.